Distribution of maternal and child characteristics based on stunting status among children under five years in a primary health care setting - Nursindia A Sugoro; Jumriani Ansar; Eny Qurniyawati; Hiba Adam (Universitas Gadjah Mada, 2026)
Purpose: Stunting remains a major public health concern in Indonesia, particularly among children under five, as it is linked to impaired growth and developmental outcomes. This study aimed to describe the distribution of maternal and child characteristics according to stunting status in a primary health care setting. Methods: A cross-sectional study was conducted among children under 5 years of age (0–59 months) using systematic random sampling (n = 110). Data were collected through structured interviews with mothers and supplemented by health center records. Stunting status was determined using height-for-age z-scores from the 2020 Primary Health Care Center report, in accordance with standard child growth monitoring practices. A bivariate analysis using the chi-square test was conducted to examine crude associations between maternal and child characteristics and stunting. Results: Stunting was more common among children whose mothers had lower nutritional knowledge, lower educational attainment, and shorter maternal height. A higher proportion of stunting was also observed among children with a history of infectious diseases and those with limited access to health services. Maternal nutritional knowledge, maternal education, maternal height, history of infectious diseases, and access to health services were statistically associated with stunting (p < 0.05), while household income was not (p = 0.094). Conclusion: Several maternal and child characteristics were statistically associated with stunting at the bivariate level. These findings highlight the importance of strengthening maternal education, nutrition counseling, infection prevention, and access to primary health care services. However, the results should be interpreted cautiously as they reflect crude associations rather than independent effects.